Perilaku Merokok pada Siswa SMA - Hasmaul yunanda; Caecielia Makaginsar; Susan Fitriyana (Bandung Conference Series: Medical Science, 2023)
Abstract. For adolescents, smoking is a symbolic thing because it can make them look stronger and more mature. Smoking is considered by adolescents to provide peace, reduce feelings of anxiety, and make it easier to concentrate. Smoking has both positive and negative impacts on adolescents. This study aims to determine smoking behavior among high school students at SMAN 2 Sungai Limau in 2022. This research was conducted in August 2022 with an analytic observational design using a cross-sectional study. The subjects of this study were 115 high school students who met the inclusion and exclusion criteria and were selected by the consecutive sampling technique. Primary data was collected by completing a validated smoking behavior questionnaire. The results showed that most of the respondents had a light smoking behavior of as much as 82.6%. Light smoking behavior is because in the area of West Sumatra, on average, every child from the age of four has studied religion and recited the Quran in a surau or mosque. Because they are equipped with religious knowledge from an early age, this is enough to equip students with the knowledge that smoking is prohibited and causes more harm. Abstrak. Bagi remaja, merokok adalah hal yang simbolis karena bisa menjadikan dirinya seseorang yang terlihat lebih kuat, matang, dan dewasa. Merokok dianggap oleh remaja memberikan ketenangan, mengurangi perasaan gelisah, dan berkonsentrasi jadi lebih mudah. Merokok memiliki dampak positif dan negatif pada remaja. Penelitian ini bertujuan untuk mengetahui perilaku merokok pada siswa SMA di SMAN 2 Sungai Limau pada tahun 2022. Penelitian ini dilakukan pada Agustus 2022 dengan desain analytic observational menggunakan studi cross-sectional. Subjek penelitian ini berjumlah 115 siswa SMA yang memenuhi kriteria inklusi dan eksklusi serta dipilih dengan teknik consecutive sampling. Pengumpulan data diambil melalui data primer dengan pengisian kuesioner perilaku merokok yang telah tervalidasi. Hasil penelitian menunjukkan bahwa sebagian besar responden memiliki perilaku merokok ringan sebanyak 82,6%. Perilaku merokok ringan dikarenakan di daerah Sumatera Barat rata-rata setiap anak dari umur empat tahun sudah belajar ilmu agama dan mengaji di surau atau masjid. Dikarenakan dibekali ilmnu agama sejak dini, hal tersebut cukup untuk membekali pengetahuan siswa bahwa rokok hukumnya makruh serta lebih banyak mudaratnya.